Harvest of Hope : Family Farming/Farming Families - Garkovich, Lorraine, 1950- (Book collections on Project MUSE., 2015)
The image of the family farm as storehouse of the traditional values that built this nation -- self-reliance, resourcefulness, civic pride, family strength, concern for neighbors and community, honesty, and friendliness -- persists, as many recent surveys show. But the reality of this rich tradition is rapidly changing, eroding the security once represented by these nostalgic images of rural America. Although the United States is still by far the world's leading overall producer of agricultural products, the number of American families making their livelihood through farming is much diminished,